Early‐season plant cover supports more effective pest control than insecticide applications. Issue 5 (30th May 2022) - Rowen, Elizabeth K.; Pearsons, Kirsten A.; Smith, Richard G.; Wickings, Kyle; Tooker, John F.
Abstract: Growing evidence suggests that conservation agricultural practices, like no‐till and cover crops, help protect annual crops from insect pests by supporting populations of resident arthropod predators. While adoption of conservation practices is growing, most field crop producers are also using more insecticides, including neonicotinoid seed coatings, as insurance against early‐season insect pests. This tactic may disrupt benefits associated with conservation practices by reducing arthropods that contribute to biological control. We investigated the interaction between preventive pest management (PPM) and the conservation practice of cover cropping. We also investigated an alternative pest management approach, integrated pest management (IPM), which responds to insect pest risk, rather than using insecticides prophylactically. In a 3‐year corn ( Zea mays mays L.)–soy ( Glycine max L.) rotation, we measured the response of invertebrate pests and predators to PPM and IPM with and without a cover crop. Using any insecticide provided some small reduction to plant damage in soy, but no yield benefit. In corn, vegetative cover early in the season was key to reducing pest density and damage, likely by increasing the abundance of arthropod predators. Further, PPM in year 1 decreased predation compared to a no‐pest‐management control. Contrary to our expectation, the IPM strategy, which required just one insecticide application, was more disruptive to the predator community than PPM, likely because the applied pyrethroid was more acutely toxic to a wider range of arthropods than neonicotinoids. Promoting early‐season cover was more effective at reducing pest density and damage than either intervention‐based strategy. Our results suggest that the best pest management outcomes may occur when biological control is encouraged by planting cover crops and avoiding broad‐spectrum insecticides as much as possible. As part of a conservation‐based approach to farming, cover crops can promote natural‐enemy populations that can help provide biological effective control of insect pest populations.